2012
DOI: 10.1111/j.2042-3306.2012.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of head and neck position on radiographic measurement of intervertebral distances between thoracic dorsal spinous processes in clinically sound horses

Abstract: SummaryReasons for performing study: Reductions in distances between dorsal spinous processes on radiographs are used as criteria for the diagnosis of impingement of the thoracic dorsal spinous processes in horses but are potentially altered by spine motion and different head and neck positions. Objectives: To determine the influence of head and neck positions on intervertebral distances between dorsal spinous processes on radiographs of thoracic spines of clinically sound horses. Methods: Lateral-lateral radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…The intervertebral DSP distances can also be altered by changing the head and neck position of a horse (Berner 2012). Flexion of the cranial spine and extension of the caudal spine, which is achieved by lowe-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervertebral DSP distances can also be altered by changing the head and neck position of a horse (Berner 2012). Flexion of the cranial spine and extension of the caudal spine, which is achieved by lowe-…”
Section: Discussionmentioning
confidence: 99%
“…Pferdeheilkunde 31 (2015) 464 ring the head position, leads to reduction of the distances between adjacent dorsal spinous processes (Berner 2012). Penell et al (2007) reported this effect after sedation, which is commonly used to facilitate radiography of the equine thoracolumbar spine.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the head and neck also influences the apparent distance between the thoracic DSPs, confounding the issue (Berner et al . ).…”
Section: Radiographic Assessmentmentioning
confidence: 97%
“…The second study in the imaging session that was featured in the EVJ supplement focused on the effects of positioning on the radiographic distances measured between thoracic dorsal spinous processes . Back pain in horses may be caused by the impingement of nerves between dorsal spinous processes of the thoracic vertebrae, and the diagnosis of impingement is made by measuring the radiographic distance between the processes.…”
Section: Diagnostic Imagingmentioning
confidence: 99%